THE EFFECT OF QUANTUM TEACHING LEARNING MODEL WITH TRI KAYA PARISUDHA TOWARD NARTURAL SCIENCE LEARNING OUTCOME - I Gede Yoga Ariana; I Gusti Ayu Tri Agustiana; I Ketut Dibia (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research aims to figure out the effect of quantum teaching learning model with Tri Kaya Parisudha toward natural science learning outcomes. This research was an experimental research design with non-equivalent post-test only control group.. The research populations were all fourth grades students of cluster III Kintamani academic years 2019/2020 with 127 students in total. Research sample was determined through simple random sampling with lottery; as a result, 22 fourth grades students of SDN Abuan became the experimental class and 20 fourth grades students of SDN Bayung Gede became the control group. Data collection used was natural science learning outcomes test. The data were analyzed through t-test. Based on the analysis, this research portrayed that there was an effect of quantum teaching learning model with Tri Kaya Parisudha toward natural science learning outcomes. The analysis result showed that t-score was 4.879 while t-table with 5% significance was 2.021. The average score of the group that got quantum teaching learning model with Tri Kaya Parisudha treatment was 20.27 with high category, and the average score of the group that did not get quantum teaching learning model with Tri Kaya Parisudha treatment was 13.85 with medium/normal category. It meant that the average score of the group that got quantum teaching learning model with Tri Kaya Parisudha treatment was higher than the average score of the group that did not get the same treatment.